The impact of internal organization factors on the adoption of e-commerce and its effect on organizational performance among Palestinian small and medium enterprise - Herzallah, Fadi; Mukhtar, Muriati (2015)
Electronic Commerce (EC) can without a doubt help firms reduce cost, enhance efficiency, and expand their market reach.However, small and medium sized enterprises in Palestine are slow in adopting EC.As a result, it became important to analyse the situation and determine the factors affecting the implementation process.Numerous firms encounter hurdles during the EC dispersion process, thus, failing to gain any benefits from EC adoption.The paper aims to determine the technological, organizational, and information culture factors that have an impact on EC adoption process, and how EC adoption in turn affects the organization’s performance.A quantitative research technique using the survey method will be used in this research.The technology-organization-environment-framework known as TOE framework is the base upon which the paper proposed an integrated model to study the effects of factors from the technological, organizational, and informational culture points of view during the EC process adoption. Information culture factors have gained more focus; as they have hardly been examined by previous literature regarding their influence on EC adoption.For the specific objective of this study, Palestine has been chosen to examine how information culture factors influence EC adoption during the diffusion process, not only providing practical guidelines for enterprises engaging in EC adoption, but also providing academics an insight on the EC adoption process perspective, particularly during diffusion of EC.